Official launch of the AWARE platform for strengthening anticipatory action in Sri Lanka - Alahacoon, Niranga; Amarnath, Giriraj; Dickowita, Ranoja (International Water Management Institute, 2025)
The AWARE Launch Workshop marked a significant milestone in strengthening Sri Lanka’s shift from reactive disaster response to a proactive, anticipatory action framework. Developed by the International Water Management Institute (IWMI) in close partnership with the Disaster Management Centre (DMC) and national technical agencies, including the Meteorological Department, the Irrigation Department, and the National Building and Research Organization (NBRO), the AWARE Platform is an advanced digital platform designed to enhance Early Warning, Early Action, and Early Finance. Combining climate and hydrological forecasts, Earth observation monitoring, and predictive analytics, AWARE equips decision-makers with timely, localized insights on floods, droughts, landslides, and climate-related health risks. At the workshop, senior representatives from DMC, NBRO, and IWMI officially launched the platform, highlighting its alignment with national disaster management priorities and with the global Early Warnings for All (EW4All) initiative. Participants received an in-depth introduction and live demonstration showcasing AWARE’s dynamic dashboards, automated anticipatory action thresholds, rapid flood mapping using Sentinel-1 data, and customizable triggers down to the Division level. Discussions emphasized the platform’s growing role in improving coordination, strengthening institutional readiness, and supporting transparent early-finance mobilization. Experts from the government, UN agencies, and NGOs provided constructive feedback on data integration, localized hazard modelling, system sustainability, and user accessibility. The workshop concluded with a shared commitment to further co-development, expanded training, and piloting AWARE during the upcoming monsoon season to enhance Sri Lanka’s resilience to climate-induced disasters.